Inequalities in Access of Learning in Primary School: Voices from Children with Special Needs - Sukadari; Jandra, Mifedwil; Huda, Miftachul; Maseleno, Andino (International Journal of Psychosocial Rehabilitation, 2020)
The objective of the research concerned here was to know the factors that hinder the accessibility of children with special needs in their education at inclusive primary school. The research sample consisted of 100 children with special needs who were having education at 20 inclusive primary schools in four districts, in particular region of Yogyakarta, Indonesia. Through questionnaire use, documentation, and structured and in-depth interviews, the data were analysed descriptively in quantitative and qualitative manners. The results indicated that this study seems to be quite a complicated and complex problem to realize the accessibility for children with special needs at inclusive primary school. The core point of this attainment refers to the realization of the accessibility still encountering many hindrances because it is very complicated and expensive and the government is quite limited in its resources and so on. Moreover, the realization of accessibility in public facilities for children with special needs only a matter of the good will of the policy maker to enforce the policy concerned and the will of the educational institution to always safeguard the enforcement of the policy. The significant value to enhance the entire attempts on realizing the accessibility in the education at inclusive primary school should be considered to give insights into regaining the human dignity of minority groups, which include children with special needs.